STRATEGI KEPALA SEKOLAH DALAM MENGELOLA KONFLIK DAN PERILAKU ORGANISASI DI SMA PGRI SITURAJA - Muhamad Rifai Suhendra; Wahyu Hidayat (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Conflict will have a positive value if it can be managed properly through conflict management that is built by a leader. The principal becomes the leader or leader in running the organization of school education institutions. The role of the Situraja PGRI SMA principal is certainly required to be able to manage the conflicts that occur at the Situraja PGRI SMA. This study aims to find out how the principal's strategy is in managing conflict and organizational behavior that occurs in SMA PGRI Situraja. The method used in this research is qualitative research and the type of research includes field research. The results of this study indicate that school principals manage conflict with strategies of collaboration, accommodation and compromise. Through these three ways of handling conflict the school principal is proven to be able to prevent, avoid, and be able to minimize the impact of conflict in the SMA PGRI Situraja school environment, as well as the realization of teamwork performance where the principal and all teachers can contribute according to their capacities and abilities so that stakeholders can achieve the best results in seeking the right solution.